Ineffectual Targeting of HIV-1 Nef by Cytotoxic T Lymphocytes in Acute Infection Results in No Functional Impairment or Viremia Reduction - De La Cruz, Justin (American Society for Microbiology, 2014)
The human immunodeficiency virus type 1 (HIV-1) accessory protein Nef is heavily targeted by CD8(+) T lymphocytes (CTLs) during acute infection and therefore is included in many candidate vaccines. We investigated whether CTL targeting of Nef during acute infection contributes to immune control by disrupting the function of Nef. The sequence and function of Nef in parallel with CTL responses were assessed longitudinally from peak viremia until the viremia set point in a cohort of six subjects with acute infection. All but one individual had a single founder strain. Nef-specific CTL responses were detected in all subjects and declined in magnitude over time. These responses were associated with mutations, but none of the mutations were detected in important functional motifs. Nef-mediated downregulation of CD4 and major histocompatibility complex (MHC) class I molecules was better preserved in acute infection than in chronic infection. Finally, Nef-specific CTL responses were not associated with a reduction in viremia from its acute-phase peak. Our results indicate that CTLs targeting Nef epitopes outside critical functional domains have little effect on the pathogenic functions of Nef, rendering these responses ineffective in acute infection. IMPORTANCE These data indicate that using the whole Nef protein as a vaccine immunogen likely allows immunodominance that leads to targeting of CTL responses that are rapidly escaped with little effect on Nef-mediated pathogenic functions. Pursuing vaccination approaches that can more precisely direct responses to vulnerable areas would maximize efficacy. Until vaccine-induced targeting can be optimized, other approaches, such as the use of Nef function inhibitors or the pursuit of immunotherapies such as T cell receptor gene therapy or adoptive transfer, may be more likely to result in successful control of viremia.